(untitled) (Research, Society and Development, 2020)
Pasta is a food that stands out for its rich carbohydrates, besides being rich in starch and low in fat content, being highly valued its enrichment by proteins and vitamins and minerals, to improve the diet of those who consume it, but it has a low concentration of proteins in its composition. Therefore, the objective of this work was to elaborate and evaluate the nutritional characteristics of pasta, with partial replacement of wheat flour by okara flour, aiming to increase the protein and fiber content. Five formulations with different concentrations of okara (0, 5, 10, 15 and 20%) and analyzed for technological characteristics and moisture content for, lipids, proteins, fibers and ash. It is concluded that the addition of “okara” flour in the pasta formulations increased the protein value, the fiber and total mineral content of the samples.